PERANAN ORANG TUA DALAM PEMBENTUKAN MORAL SISWA DI SD NEGERI TABAM KECAMATAN KOTA TERNATE UTARA - Rustam Hasyim (PEDAGOGIK, 2014)
This research discussed about the role of parents in develops childrens morality in Tabam North Ternate. The background of this research explained about the moral develops of the childrens in families and their growth. Spouse are the genetics for their generation to develops their attitudes. The environment is the key of childrens behavior while taking car of children is not a simple way, they need their parent’s guideing.This research used naturalistic qualitative approach to describe the parent’s role inside childrens natural behavour. Naturalistic qualitative approach used to perceive the information deeply about the parents participation in develop and create childs behavior, with techincs by observation, interview, and documentation. Interview used in this research to reach the information based on the questions.Summary of this research are while the education parents has influences to the childrens morality that can be aplicated by the children at the school and community. Spouse with their standard education level will influence to their childrens behavior. Key Words: parents, students, Morality, Tabam elementary school